The Influence Of Family Satisfaction And School Satisfaction Towards Psychological Well-Being Among High School Students In Iran - Sadeghi, Minoo (2015)
Kajian ini bermatlamat mengkaji kesejahteraan psikologi pelajar berdasarkan kepuasan keluarga dan sekolah. Kepuasan keluarga dipengaruhi oleh kohesi, kebolehsuaian dan komunikasi. Sebaliknya, kepuasan sekolah dipengaruhi oleh sikap terhadap sekolah, sikap terhadap guru, persepsi diri terhadap akademik, penilaian matlamat dan motivasi. Berdasarkan matlamat kajian ini, objektif berikut dipenuhi. Pertama, tahap kesejahteraan psikologi pelajar didokumentasikan. Kedua, usaha dijalankan untuk mengenal pasti perbezaan status kesejahteraan psikologi pelajar berdasarkan gender dan kumpulan umur. Seterusnya, kajian mengkaji sumbangan kohesi, kebolehsuaian dan komunikasi keluarga terhadap variasi kesejahteraan psikologi pelajar. Yang terakhir, persepsi diri terhadap akademik, motivasi, sikap terhadap sekolah, sikap terhadap guru dan penilaian matlamat turut dikaji berhubung dengan sumbangan setiap faktor terhadap kesejahteraan psikologi pelajar. Tiga model yang menyokong teori yang dibahas turut digunakan. Pertama, model Ryff, yang menyokong hujah tentang kesejahteraan psikologi pelajar. Kedua, model Circumplex, yang menjelaskan tentang kepuasan keluarga. Ketiga, model McCoach, yang menyokong hujah tentang kepuasan sekolah. This study aims to examine students’ psychological well-being based on family and school satisfaction. Family satisfaction is influenced by cohesion, flexibility and communication. On the other hand, school satisfaction is influenced by attitude towards school, attitude towards teacher, academic self-perception, goal valuation, and motivation. According to the aim of this study the following objectives were to be fulfilled. First, the level of psychological well-being of students had to be determined. Secondly, an attempt was made to identify the differences of the status of students’ psychological well-being based on gender and age group. Next, the study examined the contribution of cohesion, flexibility and communication towards the variation of students’ psychological well-being. Finally, academic self-perception, motivation, attitude towards school, attitude towards teacher and goal valuation were examined with regard to their contributions to students’ psychological well-being. Three models that support theoretic argument of this study were used. Ryff‘s model that defends psychological well-being argument, Circumplex Model that asserts family satisfaction subject and, finally, McCoach’s model that supports the argument of school satisfaction.